Civil Society’s Role in Indonesia’s Humanitarian Diplomacy: Study of Indonesian Religious Organizations' Humanitarian Aid in the Crisis in Myanmar's Rakhine State Region (2012- 2018) - Jatmika, Muhammad Indrawan; Anggraheni, Palupi (POLITEA, 2021)
Civil Society is considered as the third space outside the state and market where people can express their opinions and make certain contributions to create a condition in accordance with the certain values they profess. As the time progresses, with the development of information and globalization, the demand for bigger civic space is undeniable and the need for society to be able to contribute to an issue that occurs outside the border of their country is arising. This encourages the role of civil society to contribute to humanitarian diplomacy efforts where the role of the community and non-state actors is needed in solving transnational problems. This issue is exemplified by the role of various religious organizations in Indonesia through their contribution in helping to solve humanitarian problems in Rakhine State, of Myanmar between 2012 to 2018. Through a humanitarian diplomacy approach, these various religious organizations collaborated with the Indonesian government to send various types of assistance. This paper will explain why the role of religious organizations in Indonesia as the representation of civil society is significant in the humanitarian diplomacy effort of the Rakhine State Crisis. This paper will also provide a descriptive narrative related to how these contributions are channelled and delivered to the conflict-affected communities in Myanmar.